Reproductive performance of Ile de France ewes under dietary supplementation before and during the breeding season - Cirne, Luís Gabriel Alves; Da Silva Sobrinho, Américo Garcia [UNESP]; Oliveira, Maria Emilia Franco [UNESP]; Barbosa, José Carlos [UNESP]; De Oliveira, Gabriel Jorge Carneiro; Bagaldo, Adriana Regina; De Carvalho, Gleidson Giordano Pinto; Moreno, Greicy Mitzi Bezerra (Universidade Estadual de Londrina, 2016)
The aim of this study was to evaluate the reproductive performance of Ile de France ewes undergoing dietary supplementation before and during the breeding season, with and without association with management conditions (pre-mating shearing). Thirty-six ewes with an average body weight of 66 kg were used in the experiment. Treatments involved ewes receiving or not receiving concentrate supplementation (flushing), with groups subdivided according to the management condition to which animals were subjected: shearing or lack of it. Thus, ewes were divided into four treatments: flushed and shorn; flushed and unshorn; unflushed and shorn; and unflushed and unshorn. Flushing increased weight gain and body condition score, and when associated with shearing, it promoted anticipation of estrus. Fertility rate (86.05%), calving rate (77.77%), birth rate (113.83%), and type of birth (single: 82.29% and twin: 17.71%) were not influenced. Birth weight (3.96 kg) and prolificacy (1.25%) also were not affected. Despite the lack of changes in reproductive traits, flushing adopted during the breeding season associated with shearing anticipated estrus in ewes.
Keywords: Flushing; Management; Reproduction; Shearing; Sheep